Sulfonated, oxidized pectin-based double crosslinked bioprosthetic valve leaflets for synergistically enhancing hemocompatibility and cytocompatibility and reducing calcification. Issue 40 (29th September 2022) - Hu, Mengyue; Peng, Xu; Shi, Shubin; Wan, Chang; Cheng, Can; Lei, Ningning; Yu, Xixun
Abstract : The synergistic strategy of sulfonated, oxidized pectin and quercetin can enhance the BVLs' mechanical properties and also endow BVLs with excellent hemocompatibility, anti-inflammatory, anti-calcification, and pro-endothelialization. Abstract : Clinically frequently-used glutaraldehyde (GA)-crosslinked bioprosthetic valve leaflets (BVLs) are still curbed by acute thrombosis, malignant immunoreaction, calcification, and poor durability. In this study, an anticoagulant heparin-like biomacromolecule, sulfonated, oxidized pectin (SAP) with a dialdehyde structure was first obtained by modifying citrus pectin with sulfonation of 3-amino-1-propane sulfonic acid and then oxidating with periodate. Notably, a novel crosslinking approach was established by doubly crosslinking BVLs with SAP and the nature-derived crosslinking agent quercetin (Que), which play a synergistic role in both crosslinking and bioactivity. The double crosslinked BVLs also presented enhanced mechanical properties and enzymatic degradation resistance owing to the double crosslinking networks formed via CN bonds and hydrogen bonds, respectively, and good HUVEC-cytocompatibility. The in vitro and ex vivo assay manifested that the double-crosslinked BVLs had excellent anticoagulant and antithrombotic properties, owing to the introduction of SAP. The subcutaneous implantation also demonstrated that the obtained BVLs showed a reduced inflammatory response and great resistance to calcification, which is attributed to quercetin with multiple physiological activities and depletion of aldehyde groups by hydroxyl aldehyde reaction. With excellent stability, hemocompatibility, anti-inflammatory, anti-calcification, and pro-endothelialization properties, the obtained double-crosslinked BVLs, SAP + Que-PP, would have great potential to substitute the current clinical GA-crosslinked BVLs.